Structural Evolution of the Mesopotamia Plain - Hamid Al-Shammary, Dr. Sarteel (Journal of College of Education, 2021)
The geological setting of the Mesopotamia Plain of the central and south parts of Iraq is a part of the Mesopotamia fore deep with the tectonic framework of Iraq. The Mesopotamia Plain is a large subsiding basin covered by thick Quaternary sediments of the Tigris and Euphrates Rivers with their tributaries and distributaries. It has been receiving pre-Quaternary sediments from the adjacent rising mountains, in the north, northeast and east, and from the Inner Platform, in the west and south, too. The Mesopotamia Plain is a mobile tectonic zone and contains several buried structures including folds and faults. Recent tectonic activity of some of these structures is recorded through their effects on the Quaternary stratigraphy and present geomorphological landforms, such as abandoned river channels, active and inactive alluvial fans and topographic expressions of some active subsurface anticlines, all together indicating Neotectonic activity of the plain.